(untitled) (Eureka Journal of Education & Learning Technologies, 2025)
This article outlines the pedagogical conditions for using digital technologies in the process of developing speech competencies in learners of the Uzbek language. The main purpose of the study is to develop a pedagogical model that ensures the effectiveness of speech development through digital technologies and to test this model through practical experimentation. The research analyzes the influence of the digital learning environment on speech development, the methodological role of the teacher, factors that increase learners’ engagement, and the didactic potentials of modern interactive tools.